The Model of the Success of Settlement Twinning in the Hungarian-Croatian Cross-Border Region - Krisztina Keller; Kristina Svržnjak; Nikoletta Kaszás (DETUROPE)
The number of twin settlement relations grows continuously in the European countries, including Hungary and Croatia as well. During our quantitative research we examined the inhibitory factors of twin settlement co-operations, the nature of relationships, taking into account the current content of relationships as well. We have also mapped, what benefits the questioned local authorities can expect from the co-operation, which target groups are involved in this, and how intensively they can involve the public. The survey explored the formed municipal and county government cooperations in Zala, Somogy and Baranya counties on the Hungarian side, while on the Croatian side in Međimurska, Koprivničko križevačka, Virovitičko-podravska and Osječko-baranjskacounties. The unique nature and the importance of our work is given by the fact that we provide an answer to the question that how can the success of twin settlement relations be measured.